New technique for automatic sonographic measurement of change in head–perineum distance and angle of progression during active phase of second stage of labor. (1st October 2020) - Angeli, L.; Conversano, F.; Dall'Asta, A.; Volpe, N.; Simone, M.; Di Pasquo, E.; Pignatelli, D.; Schera, G. B. L.; Di Paola, M.; Ricciardi, P.; Ferretti, A.; Frusca, T.; et al.
ABSTRACT: Objective: To evaluate the performance of a new ultrasound technique for the automatic assessment of the change in head–perineum distance (delta‐HPD) and angle of progression (delta‐AoP) during the active phase of the second stage of labor. Methods: This was a prospective observational cohort study including singleton term pregnancies with fetuses in cephalic presentation during the active phase of the second stage of labor. In each patient, two videoclips of 10 s each were acquired transperineally, one in the axial and one in the sagittal plane, between rest and the acme of an expulsive effort, in order to measure HPD and AoP, respectively. The videoclips were processed offline and the difference between the acme of the pushing effort and rest in HPD (delta‐HPD) and AoP (delta‐AoP) was calculated, first manually by an experienced sonographer and then using a new automatic technique. The reliability of the automatic algorithm was evaluated by comparing the automatic measurements with those obtained manually, which was considered as the reference gold standard. Results: Overall, 27 women were included. A significant correlation was observed between the measurements obtained by the automatic and the manual methods for both delta‐HPD (intraclass correlation coefficient (ICC) = 0.97) and delta‐AoP (ICC = 0.99). The high accuracy provided by the automatic algorithm was confirmed by the high values of the coefficient of determination ( r 2 = 0.98 for both delta‐HPD and delta‐AoP) and the low residual errors (root mean square error = 1.2 mm for delta‐HPD and 1.5° for delta‐AoP). A Bland–Altman analysis showed a mean difference of 0.52 mm (limits of agreement, −1.58 to 2.62 mm) for delta‐HPD ( P = 0.034) and 0.35° (limits of agreement, −2.54 to 3.09°) for delta‐AoP ( P = 0.39) between the manual and automatic measurements. Conclusions: The automatic assessment of delta‐AoP and delta‐HPD during maternal pushing efforts is feasible. The automatic measurement of delta‐AoP appears to be reliable when compared with the gold standard manual measurement by an experienced operator. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd.